(3HSJGf GdGWHGA hQhVI GdGdHGAs - (3ehGab GdOjf CHj fUQ GSYO Hf GdjGS GHf GdeWQGf,J (B587 (3g` s
(3ChdgG (B:s
(3bGd GdTjN GQHYI CYVGA ai HGWf GdHOf dGjMS HGdhLY hgj GdeQi hGdcHO hGdWMGd hGdcdi s
(3BNQgG (B:s
(3hbGd GYde Gf GdGYQGV bSeGf GMOgeG eG jchf Yf GdWHjYI hGdKGfi eG jchf Yf GdeQVi hGdPi jchf Yf GdWHjYI cGdbTYQjQI hfMhgG hGdPi jchf Yf GdeQV cGdUOGY GdJGHY ddMei GdOGjeI s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGfis
(3HgG fXGe GdJYbjHIs
(3JfJgi HhbaI cGJHs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B293s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B243s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdWHs